Didactica limbii engleze. Partea I - ȚAULEAN, Micaela (Presa Universitară Clujeană, 2023)
The book provides the students with a theoretical framework based on the methodology and practice-oriented issues. Learning a language consists of acquiring language systems (vocabulary, pronunciation and grammar) and developing language skills (listening, speaking, reading and writing).